Tyrosine Kinase Receptor Expression in Canine Liposarcoma. (March 2017) - Avallone, G.; Pellegrino, V.; Roccabianca, P.; Lepri, E.; Crippa, L.; Beha, G.; De Tolla, L.; Sarli, G.
The expression of tyrosine kinase receptors is attracting major interest in human and veterinary oncological pathology because of their role as targets for adjuvant therapies. Little is known about tyrosine kinase receptor (TKR) expression in canine liposarcoma (LP), a soft tissue sarcoma. The aim of this study was to evaluate the immunohistochemical expression of the TKRs fibroblast growth factor receptor 1 (FGFR1) and platelet-derived growth factor receptor–β (PDGFRβ); their ligands, fibroblast growth factor 2 (FGF2) and platelet-derived growth factor B (PDGFB); and c-kit in canine LP. Immunohistochemical labeling was categorized as high or low expression and compared with the mitotic count and MIB-1–based proliferation index. Fifty canine LPs were examined, classified, and graded. Fourteen cases were classified as well differentiated, 7 as myxoid, 25 as pleomorphic, and 4 as dedifferentiated. Seventeen cases were grade 1, 26 were grade 2, and 7 were grade 3. A high expression of FGF2, FGFR1, PDGFB, and PDGFRβ was identified in 62% (31/50), 68% (34/50), 81.6% (40/49), and 70.8% (34/48) of the cases, respectively. c-kit was expressed in 12.5% (6/48) of the cases. Mitotic count negatively correlated with FGF2 ( R = –0.41; P < .01), being lower in cases with high FGF2 expression, and positively correlated with PDGFRβ ( R = 0.33; P < .01), being higher in cases with high PDGFRβ expression. No other statistically significant correlations were identified. These results suggest that the PDGFRβ-mediated pathway may have a role in the progression of canine LP and may thus represent a promising target for adjuvant cancer therapies.